A study on bending capacity of wall-slab structural system by using single layer and double layer of rebar for residential project / Hooi Min Yee and Siti Isma Hani Ismail - Hooi, Min Yee; Ismail, Siti Isma Hani (2012)
Using Industrialised Building Systems (IBS) will address issues such as quality, materials wastage, delays, dirty and hazardous worksites. Wall-slab structural system is in the form of rigidly connected wall slab member.Moment transfer of joint is an important aspect for proper structurally functioning of wall-slab system. The objective of this study is to investigate the effect of reinforcement details in the wall on bending capacity for support stiffness in wallslab. A total of six wall specimens were tested. Three of these specimens consisted single layer of rebar while another three specimen consisted of double layer of rebar. The size of the wall-slab's specimens is 1000mm in length, 1080mm in width, 1000mm in height and 80mm in thickness. The predicted bending capacity at failure is from 5.36k6m to 7.12k6m, depending on actual concrete cover. The bending capacity at failure for single layered of rebar in wall for specimen 1, 2 and 3 were found to be 3.59k6m, 3.81k6m and 3.15k6m, respectively. The bending capacity at failure for double layered of rebar in wall for specimen 1, 2 and 3 were 5.50k6m, 6.31k6m and 7.00k6m, respectively. Based on the results, specimens consisted of double layered of rebar in wall are found to provide higher bending capacity to the joint of wall-slab structural system compared with single layered of rebar in wall.